Efflux pump ABCB1 single nucleotide polymorphisms and dose reductions in patients with metastatic renal cell carcinoma treated with sunitinib. (October 2014) - Beuselinck, Benoit; Lambrechts, Diether; Van Brussel, Thomas; Wolter, Pascal; Cardinaels, Nina; Joniau, Steven; Lerut, Evelyne; Karadimou, Alexandra; Couchy, Gabrielle; Sebe, Philippe; Ravaud, Alain; Zerbib, Marc; et al.
Abstract There is growing evidence that sunitinib plasma levels have an impact on treatment outcome in patients with metastatic renal cell carcinoma (mRCC). We studied the impact of single nucleotide polymorphisms (SNPs) in genes involved in sunitinib pharmacokinetics, and additionally, sunitinib pharmacodynamics on dose reductions of the tyrosine kinase inhibitor. Methods. We retrospectively analyzed germ-line DNA retrieved from mRCC patients receiving sunitinib as first-line therapy. We genotyped 11 key SNPs, respectively, in ABCB1, NR1/2, NR1/3 and CYP3A5, involved in sunitinib pharmacokinetics as well as VEGFR1 and VEGFR3, which have been suggested as regulators of sunitinib pharmacodynamics. Association between these SNPs and time-to-dose-reduction (TTDR) was studied by Cox regression. Results. We identified 96 patients who were treated with sunitinib and from whom germ-line DNA and data on dose reductions were available. We observed an increased TTDR in patients carrying the TT-genotype in ABCB1 rs1125803 compared to patients with CC- or CT-genotypes (19 vs. 7 cycles; p = 0.031 on univariate analysis and p = 0.012 on multivariate analysis) and an increased TTDR in patients carrying the TT/TA-variant in ABCB1 rs2032582 compared to patients with the GG- or GT/GA-variant (19 vs. 7 cycles; p = 0.046 on univariate analysis and p = 0.024 on multivariate analysis). Conclusion. mRCC patients carrying the rs1128503 TT-variant or the TT/TA-variant in rs2032582 in ABCB1, which encodes for an efflux pump, do require less dose reductions due to adverse events compared to patients with the wild type or heterozygote variants in these genes.